2016
DOI: 10.1016/j.ejogrb.2016.07.288
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum acylated (biologically active) ghrelin and resistin levels associate with pregnancy-induced weight gain, insulin resistance and antropometric data in the fetus

Abstract: e111 and the presence of polyhydramnios, gestational age at diagnosis, lung-to-head ratio (LHR) and observed/expected LHR (O/E LHR) values, gestational age at birth and birth weight. Intrathoracic liver herniation was a statistically significant parameter adversely affecting survival (37.2% in survivors, 68.8% in non-survivors, p = 0.031) and logistic regression confirmed this relationship. The presence of pneumothorax and severe pulmonary hypertension were significantly associated with mortality (82% non-surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been suggested that disrupting the insulin signaling in insulin target tissues is the basis of insulin resistance induced by resistin. 67,[93][94][95][96] Resistin induces proliferation and migration of human endothelial cells, activation of endothelial cells by promoting endothelin-1 release, increases the expression of vascular endothelial growth factor receptors (VEGFRs) and matrix metalloproteinases (MMPs), stimulates the capillary tube formation and activates ERK1/2 and p38 pathways. 97 Thus, it seems that resistin plays a key role in angiogenesis related vascular disorders.…”
Section: Resistin: Proposed Biological Effectsmentioning
confidence: 99%
“…It has been suggested that disrupting the insulin signaling in insulin target tissues is the basis of insulin resistance induced by resistin. 67,[93][94][95][96] Resistin induces proliferation and migration of human endothelial cells, activation of endothelial cells by promoting endothelin-1 release, increases the expression of vascular endothelial growth factor receptors (VEGFRs) and matrix metalloproteinases (MMPs), stimulates the capillary tube formation and activates ERK1/2 and p38 pathways. 97 Thus, it seems that resistin plays a key role in angiogenesis related vascular disorders.…”
Section: Resistin: Proposed Biological Effectsmentioning
confidence: 99%
“…Further evidence of acyl-ghrelins' diminished action within T2D is the negative correlation between plasma fasting glucose, GHRL mRNA expression and acyl-ghrelin levels, indicating that ghrelin levels within T2D are under glucose regulation. As previously discussed in Chapter 4, the ratio of acyl-ghrelin, total ghrelin and desacyl-ghrelin within the metabolic state is controversial across published study cohorts (Rodríguez et al, 2012, Dardzińska et al, 2014, Supák et al, 2016. This ex vivo investigation of the ghrelin axis suggest that acyl-ghrelin concentrations may be dependent on GHRL expression only, and not its posttranslational modification, accounting for a lower plasma acyl-ghrelin level seen in this cohort, and reduced desacyl-ghrelin level often reported within the metabolic state (Rodríguez et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was initially deemed to be due do a decline in desacyl-ghrelin, with acyl-ghrelin being increased within obese individuals with T2D (Rodríguez et al, 2012). However, it is evident across the literature that acyl-ghrelin levels are disputed, with other reports indicating a significant decline in acyl-ghrelin levels within obese individuals with T2D (Dardzińska et al, 2014) and those with gestational diabetes (Supák et al, 2016). Within this study, there is also paradoxical evidence with data suggesting no change in acyl-ghrelin concentrations in an obese state when compared to non-obese, yet a marked decline in acyl-ghrelin levels within obese individuals with T2D.…”
Section: Inflammation Vs Acyl-ghrelinmentioning
confidence: 99%